Caracterización de la formación investigativa en un grupo de programas de Contaduría Pública acreditados en Colombia (2014)
This work is an analysis of Colombian accounting research and some considerations about the teaching required to achieve it, the first part, of huge importance, examines a recompilation of book and articles from different origins that have studied the accounting research issue, its history, methodology, techniques, methods, shades, and links with other disciplines; the second chapter relates a series of historical facts that have determinate the presence of academic spaces dedicated to de research instruction within the accounting programs from the past century until our days; the third chapter, at its time, synthesizes the characteristics of the documents subject to study, the syllabus of the academic spaces committed to the research teaching, putting in context its conditions from the perspectives of recent studies, at last, the forth chapter outlines some ideas around the improvement of the teaching practices orientated to the research teaching and proposes a full seminar.